Invitation Strategy and Learners’ Controlled Politeness: A Case in Indonesian Students of EFL - I Made Rai Jaya Widanta; Luh Nyoman Chandra Handayani; I Wayan Dana Ardika (Indonesian Journal Of Educational Research and Review, 2023)
Politeness strategies in making invitations appear to vary. The fact that there are politeness strategies in invitations of different forms covered by scientific theories raises ideas for further research. Therefore this study analyze how Indonesian learners of English as a foreign language (EFL) performed invitation strategies and controlled politeness. The research participants were 244 Indonesian learners of EFL in vocational higher education in Bali, Indonesia. The data were semantic realization of invitation performed by participants pursuant to discourse completion cards. The role play cards based on which the data were taken were divided into two divisions, role play card for hearers (Hs) with high power, high distance and high rank of imposition (P+D+R+) and low power, low distance, and high rank of imposition (P-D-R+). Data were analysed qualitatively. Analysis result revealed that there were nine new strategies of invitation. Speakers controlled politeness by a number of strategi, such as using ‘bi-clause sentences and if-conditional sentences, indirect sentences, passive sentences, formal sentences and markers such as would, could, look forward, please, Mr, Mr. director, sir, local both traditional and religious expressions, utterances with asking for permission, utterances with expression of permission, appreciation, apology to invite Hs with P+D+R+. In order to invite Hs with P-D-R+, S tended to use mono clauses and simple sentences, direct sentences, less formal sentences such as do, want, are, want, can, don’t, simple sentence, active sentences, intimacy greeting such as hallo, friends, hi guys, informal expression of suggestion, promise, imperative sentences, and direct sentences of willingness.